A flow-through enzymatic microreactor for the rapid conversion of triacylglycerols into fatty acid ethyl ester and fatty acid methyl ester derivatives for GC analysis ... - Mugo, Samuel M.; Anuar, Sabiqah T.; Curtis, Jonathan M. (University of Alberta Library, 2015)
A flow-through enzymatic microreactor for the rapid conversion of triacylglycerols (TAG) into fatty acid ethyl ester (FAEE) or fatty acid methyl ester (FAME) derivatives was developed. The microreactor was a porous silica monolith fabricated within a 320 μm ID fused silica capillary with lipase from Candida antarctica immobilized onto the large surface area of the monolith. The microreactor was used for the room temperature ethanolysis of TAG from edible oils including canola, sesame, soybean and refined-bleached-deodorized palm oil. GC/MS-NCI and GC/FID were used to prove the identification of the FAEE and FAME products. The microreactor completely transformed the starting oils into FAEEs or FAMEs, without the use of any reagents other than alcohol, in quantities suitable for GC analysis. The prototype microreactors were reusable >5 times with ethanol and 2 times with methanol. The FAEE products obtained using the microreactor were similar to those produced using commercial Novozyme 435 enzyme beads as ...